Effects of ultra pig krave extra® on starter pig performance - G R Stoner; M E Johnston; Jim L Nelssen; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1988)
A growth study and a preference study were conducted to evaluate the effect of a commercially available flavoring agent on starter pig performance. A total of 192, 3-wk old, weaned pigs were utilized. A 2-phase starter program was used in the growth study. Half the pigs received creep feed with added flavor and half without, beginning at 10 days of age. Pigs receiving flavored feed at 10 days of age had significantly better gains and feed intake the first 2 wk postweaning than pigs on nonflavored feed. The pigs in the preference study demonstrated a clear preference for flavored vs nonflavored feed. These results indicate addition of flavor to a creep diet beginning at 10 days of age will increase feed intake and gains in the nursery. However, when a creep feed is fed, addition of flavor to a nursery diet did not result in improved performance.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Pigs; Early weaning; Flavor; Creep feed